IMPLEMENTASI PROGRAM PEMBINAAN TERHADAP NARAPIDANA LANJUT USIA DI LAPAS KELAS IIB SLEMAN - Avandi, Nur Said; Subroto, Mitro (Jurnal Hukum Samudra Keadilan, 2023)
Elderly prisoners are an increasing group in the prison population worldwide. This article aims to evaluate the effectiveness of a development program specifically aimed at elderly prisoners in achieving the goals of rehabilitation and reintegration into society. This research used a combined approach involving statistical data analysis, interviews with elderly prisoners, and a literature review. The research results show that a program for developing elderly prisoners that focuses on their specific needs, such as appropriate health care, social support, skills training, and access to post-incarceration services, has a significant positive impact on improving their well-being. Apart from that, this research also identifies barriers that can reduce the effectiveness of coaching programs, such as lack of access to adequate health services, discrimination and social isolation. Therefore, it is important to integrate an approach centered on elderly prisoners in policy planning and development programs in correctional institutions. This research provides important insights for stakeholders in the criminal justice system to increase understanding of how to optimize senior prisoner development programs. Further efforts need to be made to improve the quality of these programs and ensure that elderly prisoners receive care and support appropriate to their needs to facilitate successful reintegration into society.